2011
DOI: 10.1111/j.1530-0277.2011.01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Escalation of Alcohol Drinking in C57BL/6J Mice With Intermittent Access to 20% Ethanol

Abstract: Background Intermittent access to drugs of abuse, as opposed to continuous access, is hypothesized to induce a kindling-type transition from moderate to escalated use, leading to dependence. Intermittent 24-hour cycles of ethanol access and deprivation can generate high levels of voluntary ethanol drinking in rats. Methods The current study uses C57BL/6J mice (B6) in an intermittent access to 20% ethanol protocol to escalate ethanol drinking levels. Adult male and female B6 mice were given intermittent acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
309
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(359 citation statements)
references
References 77 publications
36
309
7
Order By: Relevance
“…Consistent with previous studies in mice [Hall et al, 2001;Racz et al, 2008;Hwa et al, 2011;Yoo et al, 2012] and rats (recently reviewed by Becker and Koob 2016), we confirm sex differences in alcohol drinking, with higher alcohol intake in females. The genotype differences in alcohol intake between hypothalamic POMC deficient and wildtype mice are much greater in females than in males.…”
Section: Pro-opiomelanocortin (Pomc)/β-endorphin and Mu-opioid Resupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies in mice [Hall et al, 2001;Racz et al, 2008;Hwa et al, 2011;Yoo et al, 2012] and rats (recently reviewed by Becker and Koob 2016), we confirm sex differences in alcohol drinking, with higher alcohol intake in females. The genotype differences in alcohol intake between hypothalamic POMC deficient and wildtype mice are much greater in females than in males.…”
Section: Pro-opiomelanocortin (Pomc)/β-endorphin and Mu-opioid Resupporting
confidence: 92%
“…It was not clear, however, whether there is an involvement of β-endorphin in regulation of alcohol drinking, as earlier studies using β-endorphin deficient mice show inconsistent results by different groups [Grisel et al, 1999;Grahame et al, 2000;Racz et al, 2008] (Table 2) deficiency resulting from selective deletion of Pomc enhancers [Lam et al, 2015]. Specifically, we determine the effect of tissue-specific Pomc gene manipulation on: (a) "binge" drinking in a DID model [Rhodes et al, 2005]; (b) acquisition and escalation of excessive alcohol drinking in a chronic intermittent access (IA) model [Wise, 1973;Simms et al, 2008;Hwa et al, 2011], and (c) "relapse" drinking in an alcohol deprivation effect (ADE) model in mice of both sexes [Holter and Spanagel, 1999;Heyser et al, 2003]. The wild-type mice exposed to DID rapidly establish stable alcohol drinking behavior with more intake in females, whereas hypothalamic POMC deficient mice of both sexes have less alcohol intake and less preference.…”
Section: Pro-opiomelanocortin (Pomc)/β-endorphin and Mu-opioid Rementioning
confidence: 95%
“…The intake of a low dose of EtOH, 1% EtOH, by SAMP8 model, did not increase the drinking volume as observed for addiction. A previous study reported that C57BL/6 mice showed a high alcohol preference, escalating their drinking volume, and adaptation to the high concentration of EtOH (54). However, why the liquid consumption was lesser in the EtOH group than in the water group until about 50 weeks of age in this study remains unknown.…”
Section: Discussioncontrasting
confidence: 45%
“…In that study, rats that received intermittent access to alcohol (i.e., every other day) showed a gradual increase in alcohol intake over time. This escalation of alcohol intake over time in intermittent/every-other-day models has been confirmed by recent studies that have reintroduced this approach in the field of alcoholism research (Simms et al, 2008;Loi et al, 2010;Hwa et al, 2011;Melendez, 2011;Gilpin et al, 2012). Likewise, classic studies by Wolffgramm (1991), Wolffgramm andHeyne (1991, 1995) demonstrated that rats increase their levels of alcohol intake after lengthy periods (i.e., months) of relatively stable ethanol intake.…”
Section: Escalation Of Drug Usementioning
confidence: 67%